Avaliação da produção científica referente à incorporação de resíduos na construção (2009-2018) - Menezes, Maria Francielle Santos; Sena, Priscila Lopes dos Santos de; Santos, Débora de Gois (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
The civil construction industry is among the most degrading to the environment. With an increase in the environmental awareness in society, many alternatives were proposed in order to reduce this degradation. One of the solutions consists of the use of waste in the sector. This work aimed to perform a bibliometric analysis of the scientific production related to the use of organic and inorganic waste in the civil construction industry in the last decade. A total of 1299 papers coming from two databases were analyzed. Were also verified the main publication sources, the authors with the highest number of publications, the main collaborating institutions, the geographic distribution of the institutions that have published in the timeframe considered, the most cited sources, the most cited authors and coauthors, the most cited papers, and the total number of citations of the papers in their year of publication. This study was meant to assist future research by exposing the main work regarding this theme.